2014
DOI: 10.1186/1471-2164-15-620
|View full text |Cite
|
Sign up to set email alerts
|

The transcriptional landscape of mouse beta cells compared to human beta cells reveals notable species differences in long non-coding RNA and protein-coding gene expression

Abstract: BackgroundInsulin producing beta cell and glucagon producing alpha cells are colocalized in pancreatic islets in an arrangement that facilitates the coordinated release of the two principal hormones that regulate glucose homeostasis and prevent both hypoglycemia and diabetes. However, this intricate organization has also complicated the determination of the cellular source(s) of the expression of genes that are detected in the islet. This reflects a significant gap in our understanding of mouse islet physiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

33
249
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 253 publications
(295 citation statements)
references
References 74 publications
33
249
0
Order By: Relevance
“…While ZnT3 mRNA was reported in purified human β cells in one study [38], levels were zero, or at the limit of detection, in samples from several subjects in another [37]. ZnT3 mRNA was similarly barely detected by RNASeq in purified mouse β cells [36], in line with our findings in mouse islets [34]. The role of this particular transporter in controlling β cell Zn 2+ thus remains unclear.…”
Section: Znt Familysupporting
confidence: 82%
See 1 more Smart Citation
“…While ZnT3 mRNA was reported in purified human β cells in one study [38], levels were zero, or at the limit of detection, in samples from several subjects in another [37]. ZnT3 mRNA was similarly barely detected by RNASeq in purified mouse β cells [36], in line with our findings in mouse islets [34]. The role of this particular transporter in controlling β cell Zn 2+ thus remains unclear.…”
Section: Znt Familysupporting
confidence: 82%
“…ZnT6 mRNA was detected in the islets of Langerhans [34], its functional heterodimerization with ZnT5 has been described [35], and its presence in purified β cells from both mouse [36] and human [37,38] confirmed by massive parallel sequencing (RNASeq).…”
Section: Znt Familymentioning
confidence: 93%
“…All experiments were performed in human pancreatic islets and the human insulinproducing cell line EndoC-βH1 [24], increasing their translational potential [25][26][27][28]. The data obtained indicate that IFNα is a crucial mediator of excessive inflammation and ER stress in the early steps of type 1 diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of rodent models as a proxy for human disease comes at the risk of identifying signals that protect mouse but not human beta cells against death. For example, systematic comparison of the transcriptomes of purified mouse and human beta cells revealed that human beta cells, in contrast to mouse beta cells, express very few to no receptors for the related cytokines prolactin, GH or ciliary neurotrophic factor [13,14]. This would suggest that potential protective effects of these factors may not translate to human beta cells.…”
Section: Gfpmentioning
confidence: 98%
“…This would suggest that potential protective effects of these factors may not translate to human beta cells. Similarly, mouse beta cells express very high levels of the type 1 IL-1 receptor message and protein (Il1r1/IL1R1) [13], while the expression of IL1R1 in human islets is markedly lower and enriched in non-beta cells [14], which raises the question of whether human beta cells would show an equally robust response to an insult mediated by a cytokine cocktail that included IL-1β. Of course, in most studies on mouse beta cells [4,13] they are isolated from adults whose age is measured in months; a confounder that is difficult to avoid when using mouse beta cells to model diseases of the adult human islet.…”
Section: Gfpmentioning
confidence: 99%